PENGARUH KUALITAS PELAYANAN DAN SUASANA LINGKUNGAN TERHADAP KEPUASAN PASIEN PADA PUSKESMAS GUNUNG SINDUR KABUPATEN BOGOR - Rendy Prayoga; Muhammad Arief (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Patient satisfaction is one of the important indicators in assessing the quality of health services at community health centers (Puskesmas). Patient satisfaction is influenced by various factors, including service quality and environmental atmosphere. This study aims to determine the effect of service quality and environmental atmosphere on patient satisfaction at the Puskesmas. The research method used is a quantitative method with a survey approach. The population in this study consists of all patients who receive services at the Puskesmas, with a sample of [number] respondents determined using the [sampling technique]. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results show that the Service Quality variable (X1) has a positive and significant effect on Patient Satisfaction, with a t-count value of 6.317>1.99125 (t-table) and a significance value of 0.000<0.05. The Environmental Atmosphere variable (X2) also has a positive and significant effect on Patient Satisfaction, with a t-count value of 2.429 >1.99125 (t-table) and a significance value of 0.017<0.05. Furthermore, Service Quality and Environmental Atmosphere simultaneously have a positive and significant effect on Patient Satisfaction, as indicated by an F-count value of 22.834 with a significance value of 0.000.